2015
DOI: 10.2507/ijsimm14(3)8.303
|View full text |Cite
|
Sign up to set email alerts
|

Competition or Cooperation: a Simulation of the Price Strategy of Ports

Abstract: Ports act as the nodes connecting water transport with land transport and play pivotal roles in logistics networks. The rapid rise in international freight volume has led to a faster growth in the throughputs of many ports. With the development of containerization, services provided by different ports could be substitutable with each other, especially those in the same region which are more competitive for substitutability. However, the question must be asked: is competition unchangeable? Moreover, is competit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Common factors used to model port competition and cooperation with service level differentiation include service quality, service type, geographic location, capacity, price, profits, and welfare. Zhou [15] suggested future research could include a comparison of competition with cooperation strategies of ports serving partially overlapping hinterlands in a situation when ports compete in price and geographic location. Incorporation of more practical problems in the models that would increase the applicability of model at different settings to help robustness was suggested by Ciu and Notteboom [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Common factors used to model port competition and cooperation with service level differentiation include service quality, service type, geographic location, capacity, price, profits, and welfare. Zhou [15] suggested future research could include a comparison of competition with cooperation strategies of ports serving partially overlapping hinterlands in a situation when ports compete in price and geographic location. Incorporation of more practical problems in the models that would increase the applicability of model at different settings to help robustness was suggested by Ciu and Notteboom [16].…”
Section: Discussionmentioning
confidence: 99%
“…When the service levels of the port enterprises are different, the port's service price, market share, and profit are affected by the service level before and after the cooperation, the service level of the port enterprise shows a trend of mutual promotion, and the port group develops into a higher service level. The price strategy of ports serving partially overlapping hinterlands was investigated by Zhou [15], where the author used a modified Hotelling model and simulation to analyze the price strategy for three ports from competition and cooperation perspectives. Research results revealed that, when the service levels were the same, the critical factor for competitive ports was location, while service level was the critical factor for the creation of a port alliance.…”
Section: Port and Container Terminal Cooperation/competition And Co-omentioning
confidence: 99%
See 1 more Smart Citation
“…Ports have become a significant strategic resource for the development of national economy and regional economy in China. They act as the nodes connecting water transport with land transport and play pivotal roles in logistics network [13]. As the development of port cities and hinterland economy relies on the development of ports, a series of research on ports is of great significance for not only the development of hinterland cities, but also the development of ports themselves [11].…”
Section: Singularity Detectionmentioning
confidence: 99%
“…Asadabadi [10] developed a bi-level multiplayer game theoretic approach to study the co-opetition among ports. Zhou [11] studied the competition/cooperation between three ports with a developed Hotelling model. Wan [12] developed a spatial game model to study how the investment of local government would affect the port infrastructure with different cooperation projects.…”
Section: Introductionmentioning
confidence: 99%